Increasing Innovation and Social Media Marketing Among Women Entrepreneurs in Kampung Kerupuk Surabaya - Dewi Deniaty Sholihah (Future Science, 2022)
Women in the society 5.0 revolution have a tremendous opportunity due to gender equality to express themselves and follow their passions. Activities related to domestic affairs do not prevent women from growing. This is evidenced by the growth in Micro, Small, and Medium Scale (MSMEs), which are 90% owned and operated by women. Meanwhile, the difficulties experienced by women are considerable. One of them is the low competence required to conduct business through social media marketing. Women still have a minor role in technological advancement. On the other part, social media is a way to establish how well women can actualize themselves by creating a solid identity. In addition, social media is also another tool that is used by woman entrepreneur to promote their businesses and expand their market share. Therefore, this community service project aims to increase the knowledge and expertise of women entrepreneurs among MSMEs in Kampung Kerupuk Surabaya in using social media platforms like Instagram for both personal branding and product promotion.